From freedom fighters to jihadists: human resources of non state armed groups - Mironova, Vera (Causes and consequences of terrorism, 2019)
'From Freedom Fighters to Jihadists' examines the internal organization of armed groups, particularly their human resource practices. The author looks at the rebel armed groups through the prism of a labour market theory.